Rancher given star, award (Raton Range Raton, New Mexico, 1989)
Article on May Moore who received the Outstanding Leadership Award from New Mexico state University College of Agriculture and Home Economics and has learned a star above the sky in Switzerland has been named after her.
Master list item #:22
File location is in the Raton File Cabinet
Keywords: Moore, Mary; Owens, John; Hall, Gerald Thomas; New Mexico State University; Local History; Biography; Award; Star; Education; Raton, New Mexico; Switzerland; Las Cruces, New Mexico